Listening to the Whispers in Neuroimmune Crosstalk: A Comprehensive Workflow to Investigate Neurotrophin Receptor p75NTR Under Endogenous, Low Abundance Conditions - Dorschner, Benjamin W.; Wiedemuth, Ralf; Funke, Ann-Christin; Gentzel, Marc; Rogers, Mary-Louise; Brenner, Sebastian; Thieme, Sebastian (Frontiers in Immunology, 2021)
Inflammatory conditions are critically influenced by neuroimmune crosstalk. Cytokines and neurotrophic factors shape the responses of both nervous and immune systems. Although much progress has been made, most findings to date are based on recombinant expression of (tagged) proteins. The examination of receptor interactions by immunoprecipitation (IP) at endogenous levels provides further insight into the more subtle regulations of immune responses. Here, we present a comprehensive workflow and an optimized IP protocol that provide step-by-step instructions to investigate neurotrophin receptor p75NTR at endogenous, low abundance levels: from lysate preparation and confirmation of receptor expression to antibody validation and successful detection of protein-protein interactions. We employ human melanoma cell line A375 to validate specific antibodies and IP conditions, and apply these methods to explore p75NTR interactions in human leukemic plasmacytoid dendritic cell line PMDC05 detecting 14-3-3ε:p75NTR interaction in this cell type. With p75NTR as an exemplary protein, our approach provides a strategy to detect specific interaction partners even under endogenous, low abundance expression conditions.